A Mini-Review on Cell Cycle Regulation of Coronavirus Infection - Su, Mingjun; Chen, Yaping; Qi, Shanshan; Shi, Da; Feng, Li; Sun, Dongbo (Frontiers in Veterinary Science, 2020)
Coronaviruses are widespread in nature and infect humans, mammals and poultry. They cause harm to humans and animals. Virus-mediated cell cycle arrest is an essential strategy for viral survival and proliferation in the host cells. A clarification system of the mechanisms of virus-induced cell cycle arrest is highly desirable to promote the development of antiviral therapies. In this review, molecular mechanisms of coronavirus-induced cell cycle arrest were systematically summarized. Moreover, the common features of coronavirus-mediated cell cycle arrest were discussed. This review will provide a theoretical basis for further studies on the infection mechanisms and prevention of coronaviruses.